The effects of face-to-face versus live video-feed interviewing on children's event reports - Hamilton, Gemma (Legal and criminological psychology, 2017)
Purpose. Recent advances in technology have raised a potentially promising service to overcome difficulties associated with remote witnesses: live video-feed interviews. The efficacy of this mode of interviewing, however, lacks empirical evidence, particularly with children in an investigative context. Methods. This study explored the effects of live video-feed compared to face-to-face interviewing on the memory reports of 100 children (aged 5–12). Children participated in an innocuous event and were interviewed 1–2 days later by experienced interviewers. Results. Analyses indicated that live video-feed interviewing was just as effective as face-to-face interviewing in terms of the accuracy and informativeness of children's accounts. Video-feed interviews, however, required a higher number of clarification prompts compared to face-to-face interviews. These findings were not influenced by children's familiarity with technology. Conclusions. An initial test of live video-feed interviewing indicates it is a safe and effective method for interviewing children about an innocuous event.